2012
DOI: 10.1289/ehp.1104526
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Induces Gene Expression Changes and Proliferative Effects through GPER in Breast Cancer Cells and Cancer-Associated Fibroblasts

Abstract: Background: Bisphenol A (BPA) is the principal constituent of baby bottles, reusable water bottles, metal cans, and plastic food containers. BPA exerts estrogen-like activity by interacting with the classical estrogen receptors (ERα and ERβ) and through the G protein-coupled receptor (GPR30/GPER). In this regard, recent studies have shown that GPER was involved in the proliferative effects induced by BPA in both normal and tumor cells.Objectives: We studied the transduction signaling pathways through which BPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
158
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 250 publications
(174 citation statements)
references
References 40 publications
(63 reference statements)
13
158
1
2
Order By: Relevance
“…In addition, our and other studies have largely demonstrated the involvement of GPER in the stimulatory effects elicited by estrogens in cancer cells and tumor microenvironment (6,(9)(10)(11). Significantly, several studies performed in different cell and animal models have ascertained the role exerted by GPER in certain pathological conditions characterized by oxygen deficiency (30,31,(74)(75)(76)(77)(78).…”
Section: Gper Is Involved In Hypoxia-mediated Signalingmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, our and other studies have largely demonstrated the involvement of GPER in the stimulatory effects elicited by estrogens in cancer cells and tumor microenvironment (6,(9)(10)(11). Significantly, several studies performed in different cell and animal models have ascertained the role exerted by GPER in certain pathological conditions characterized by oxygen deficiency (30,31,(74)(75)(76)(77)(78).…”
Section: Gper Is Involved In Hypoxia-mediated Signalingmentioning
confidence: 90%
“…As demonstrated for many GPCRs (3,4), the G protein estrogen receptor (GPER, also known as GPR30) may trigger oncogenic signaling (5,6). GPER binds to estrogens, phyto-and xenoestrogens, and also estrogen receptor (ER) antagonists that may act as GPER agonists (7)(8)(9)(10)(11)(12). GPER mediates the activation of a network of transduction pathways; however, the actual role elicited by GPER in tumorigenesis is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using animal models and humans have indicated that BPA exposure might produce a broad range of adverse effects, including cancer (Weber Lozada and Keri 2011; Pupo et al 2012), disruption of meiosis and other reproductive anomalies (Allard and Colaiacovo 2010;Hunt et al 2012), impairment of genes that control brain development (Itoh et al 2012), and behavior (Kundakovic et al 2013). In some cases, the phenotypes are accompanied by disrupted expression of DNA methyltransferase 1 and 3A, two enzymes responsible for the incorporation of methyl marks on the DNA (Doherty et al 2010;Itoh et al 2012;Kundakovic et al 2013).…”
Section: Dna Methylation-independent Pathways Of Bpa Toxicitymentioning
confidence: 99%
“…12 The high frequency of detection and the rapid metabolism of orally ingested BPA suggests continuous exposure via multiple routes to substantial amounts of BPA. [13][14][15] Many articles have been published on the potentially harmful effects of BPA, including but not limited to its weak estrogenic activity, 3,16 proliferative effects on human breast cancer cells, 17 disruptive effects on both mouse and human pancreatic cells, [18][19][20][21] adverse effects on the fertility and reproductive system of female mice, 4 ability to disrupt fetal mouse prostate and urethra development, 22 and capacity to impair liver function in mice. 23 Many different orthodontic products are used routinely during and after orthodontic treatment, including but not limited to, brackets, adhesives, cements, ligatures, clear aligners, and retainers.…”
Section: Introductionmentioning
confidence: 99%